Progressive Mobility Protocol Reduces Venous Thromboembolism Rate in Trauma Intensive Care Patients: A Quality Improvement Project. Issue 5 (September 2016) - Booth, Kathryn; Rivet, Josh; Flici, Richelle; Harvey, Ellen; Hamill, Mark; Hundley, Douglas; Holland, Katelyn; Hubbard, Sandra; Trivedi, Apurva; Collier, Bryan
Abstract : The intensive care unit (ICU) trauma population is at high risk for complications associated with immobility. The purpose of this project was to compare ICU trauma patient outcomes before and after implementation of a structured progressive mobility (PM) protocol. Outcomes included hospital and ICU stays, ventilator days, falls, respiratory failure, pneumonia, or venous thromboembolism (VTE). In the preintervention cohort, physical therapy (PT) consults were placed 53% of the time. This rose to more than 90% during the postintervention period. PT consults seen within 24 hr rose from a baseline 23% pre- to 74%–94% in the 2 highest compliance postintervention months. On average, 40% of patients were daily determined to be too unstable for mobility per protocol guidelines—most often owing to elevated intracranial pressure. During PM sessions, there were no adverse events (i.e., extubation, hypoxia, fall). There were no significant differences in clinical outcomes between the 2 cohorts regarding hospital and ICU stays, average ventilator days, mortality, falls, respiratory failure, or pneumonia overall or within ventilated patients specifically. There was, however, a difference in the incidence of VTE between the preintervention cohort (21%) and postintervention cohort (7.5%) ( p = .0004). A PM protocol for ICU trauma patients is safe and may reduce patient deconditioning and VTE complications in this high-risk population. Multidisciplinary commitment, daily protocol reinforcement, and active engagement of patients/families are the cornerstones to success in this ICU PM program.